KRAS activation in gastric adenocarcinoma stimulates epithelial-to-mesenchymal transition to cancer stem-like cells and promotes metastasis - Yoon, Changhwan (Mol Cancer Res, 2019)
Our previous work showed that in a mouse model of gastric adenocarcinoma (GA) with loss of p53 and Cdh1 that adding oncogenic Kras (a.k.a. Tcon mice) accelerates tumorigenesis and metastasis. Here we sought to examine KRAS activation in epithelial-to-mesenchymal transition (EMT) and generation of cancer stem-like cells (CSCs). Transduction of nontransformed HFE-145 gastric epithelial cells with oncogenic KRAS(G12V) significantly decreased expression of the epithelial marker E-cadherin, increased expression of the mesenchymal marker vimentin and the EMT transcription factor Slug, and increased migration and invasion of by 15- to 17-fold. KRAS(G12V) also increased expression of self-renewal proteins such as Sox2 and increased spheroid formation by 2.6-fold. In tumor-derived organoids from Tcon mice, Kras knockdown decreased spheroid formation, expression of EMT-related proteins, migration, and invasion; similar effects, as well as reversal of chemoresistance, were observed following KRAS knockdown or MEK inhibition in patient tumor-derived GA cell lines (AGS and KATOIII). KRAS inhibition in GA spheroid cells led to reduced AGS flank xenograft growth, loss of the infiltrative tumor border, fewer lung metastases, and increased survival. In a tissue microarray of human GAs from 115 patients, high tumor levels of CD44 (a marker of CSCs) and KRAS activation were independent predictors of worse overall survival. In conclusion, KRAS activation in GA cells stimulates EMT and transition to CSCs, thus promoting metastasis. IMPLICATIONS: This study provides rationale for examining inhibitors of KRAS to block metastasis and reverse chemotherapy resistance in GA patients.